Research and design two-dimensional metamaterials absorber operating in the THz frequency region and applications in refractive index sensor - Trần Văn Huỳnh; Vu, Vũ Đình Lãm; Lê Thị Hồng Hiệp; Nguyễn Thanh Tùng (Journal of Military Science and Technology, 2022)
Metamaterials absorbers (MMA) are typically designed with resonators, a continuous metal plane, and a sandwiched dielectric layer. The absorption is based on losses in the dielectric layer caused by magnetic resonances. Such MMAs only allow the absorption of electromagnetic waves in the incoming direction, the electromagnetic wave is completely reflected in the opposite direction, and outside the absorption frequency region, the electromagnetic wave is also almost completely reflected. In this work, we propose an MMA structure that does not use the continuous metal plane, using Gold metal-disk pair resonators instead. MMA is designed for high absorption efficiency at a resonant frequency by overlapping magnetic and electric resonances. Simulation results show that MMA can achieve absorption efficiency up to 98% at 2.15 THz. Because there is no metal plane, MMA still allows transmission of electromagnetic waves outside the absorption frequency region, this property makes MMA more flexible and effective in THz devices.